2017
DOI: 10.1016/j.actbio.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of citrate-based fluorescent small molecules and biodegradable polymers

Abstract: Novel citric acid based photoluminescent dyes and degradable polymers are synthesized via a facile “one-pot” reaction. A comprehensive understanding of the fluorescence mechanisms of the resulting citric acid-based fluorophores is reported. Two distinct types of fluorophores are identified: a thiozolopyridine family with high quantum yield, long lifetime, and exceptional photostability, and a dioxopyridine family with relatively lower quantum yield, multiple lifetimes, and solvent-dependent band shifting behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…For example, researchers revealed the reaction possibility of citrate-based molecular fluorophores by reacting TPA (CA-Cys) and DPR (CA-Ala) structured fluorophores with 1,8-octanediol. [32, 34] LC-ESI-MS mass spectrum confirmed the ester bonds between fluorophores and diols. Fluorescence studies also showed that the resulting BPLP-TPA had identical fluorescence properties as that of CA-Cys and BPLP-Cys, including an excitation-independent emission.…”
Section: Citrate-based Molecular Fluorophoresmentioning
confidence: 88%
See 3 more Smart Citations
“…For example, researchers revealed the reaction possibility of citrate-based molecular fluorophores by reacting TPA (CA-Cys) and DPR (CA-Ala) structured fluorophores with 1,8-octanediol. [32, 34] LC-ESI-MS mass spectrum confirmed the ester bonds between fluorophores and diols. Fluorescence studies also showed that the resulting BPLP-TPA had identical fluorescence properties as that of CA-Cys and BPLP-Cys, including an excitation-independent emission.…”
Section: Citrate-based Molecular Fluorophoresmentioning
confidence: 88%
“…Yang’s group also prepared a series of CA based fluorophores via heating CA with various primary amines, amino acids, or analogs of amino acids. [32] After analyses of chemical structures and fluorescence properties, fluorescence mechanism based on TPA and DPR structures were established, depending on the choices of amines. As such, the authors proposed several amine reagents which can readily be used to prepare efficient CA based fluorescent molecules.…”
Section: Citrate-based Molecular Fluorophoresmentioning
confidence: 99%
See 2 more Smart Citations
“…The 6-membered ring structure formed by citric acid and α-amino acids has been identified to be the fluorescent moiety in BPLP. These fluorescent moieties can also be released from BPLP during degradation, as CA-Cys has been found in the alkaline hydrolysis productions of BPLP-Cys [39]. Meanwhile, a family of citratebased fluorescent small molecules have been synthesized via a one-pot reaction of citric acid with a primary amine or amino acid.…”
Section: Chemistry Considerations For Citrate-based Biomaterials Designmentioning
confidence: 99%